2016
DOI: 10.4103/2231-0746.200320
|View full text |Cite
|
Sign up to set email alerts
|

Crossed pectoralis major myocutaneous flap for recurrent oral cavity cancers

Abstract: Background:Oral cavity cancers are fairly common and have propensity to recur locally. Since Pectoralis Major Myocutaneous (PMMC) flap is the most widely used first flap for reconstruction, it is exhausted at the earliest and recurrence poses a formidable challenge for reconstructive surgeon. Present study evaluated the feasibility of contralateral Pectoralis Major Myocutaneous Flap for reconstruction after resection of recurrent tumour.Methods:This was a study of the patients presenting with recurrent oral ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…In the era of microsurgical free flaps, pedicled flaps still hold their position for the reconstruction of oral cavity cancers [13]. Study conducted by Pancholi M et al have shown PMMC flap to be easy, done early and adds to the bulk of reconstructed tissue thereby maintaining the contour especially in full thickness cheek defects post hemimandibulectomy or maxillectomy where a radial forearm flap will leave a distinct hollow due to lack of bulk [14]. In our study all the patients belonged to advanced stages of the disease, requiring marginal /hemimandibulectomy hence resulting in larger cavities all were treated with PMMC flaps and have given good results.…”
Section: Discussionmentioning
confidence: 99%
“…In the era of microsurgical free flaps, pedicled flaps still hold their position for the reconstruction of oral cavity cancers [13]. Study conducted by Pancholi M et al have shown PMMC flap to be easy, done early and adds to the bulk of reconstructed tissue thereby maintaining the contour especially in full thickness cheek defects post hemimandibulectomy or maxillectomy where a radial forearm flap will leave a distinct hollow due to lack of bulk [14]. In our study all the patients belonged to advanced stages of the disease, requiring marginal /hemimandibulectomy hence resulting in larger cavities all were treated with PMMC flaps and have given good results.…”
Section: Discussionmentioning
confidence: 99%
“…For full-thickness defects, the buccal mucosa should be corrected; commonly used regional flaps for buccal mucosal involvement include the pectoralis major myocutaneous (PMMC) flap, submental island flap, forehead flap, and latissimus dorsi flap. 13 However, forehead flaps call for a multistaged procedure that results in appreciable donor-site morbidity, whereas latissimus dorsi flaps require a change of position of the patient during the operation. 13 Therefore, only the PMMC and submental island flap are discussed herein.…”
Section: Regional Flapsmentioning
confidence: 99%
“…13 However, forehead flaps call for a multistaged procedure that results in appreciable donor-site morbidity, whereas latissimus dorsi flaps require a change of position of the patient during the operation. 13 Therefore, only the PMMC and submental island flap are discussed herein.…”
Section: Regional Flapsmentioning
confidence: 99%
See 2 more Smart Citations